Solving Pregnancy Out-of-Wedlock: ‘Dual Validity’ of Ngampang Marriage among Dayak Muslim Community in Sintang, Indonesia - Alfarisi, Muhammad Adib; Hayat, Muhammad Jihadul; Hakimi, Adul Rahim (Journal of Islamic Law, 2023)
According to most scholars of Islamic jurisprudence (jumhūr ʿulamā), marriage due to pregnancy (ngampang) is permissible as long as it is conducted under fiqh (Islamic jurisprudence) rules. Its validity is not contingent upon the situation/locus ‘in front of the state official’. It means that there is no significance in remarrying before the state official if an Islamic marriage has previously been performed beyond the walls of the state building. In reality, however, the community—in this context, the Muslim community of Sintang—often remarries before a marriage registrar to achieve state recognition in the case of marriage due to pregnancy. This article portrays how the Sintang Muslim community legalizes marriage status due to pregnancy. Data were collected through interviews. This article argues that in order to obtain state recognition of their marriage due to pregnancy, the Muslim community of Sintang often performs twofold marriage ceremonies. The first is according to customary standards (in line with the Statute of the Sintang Kingdom) and following Islamic rules. The second is according to national procedure (in front of a state official), which applies the same Islamic terms. It indicates that, in terms of resolving the issue of pregnancy out-of-wedlock, the Sintang Muslim community has to go through two standards that are not substantively contradictory to each other. Both standards actually rest on the same principles in Islamic law.